Strength of a cement-based dental material: Early age testing and first micromechanical modeling at mature age - Dohnalík, Petr; Hellmich, Christian; Richard, Gilles; Pichler, Bernhard L. A. (Frontiers in Bioengineering and Biotechnology, 2023)
The compressive strength evolution of 37 centigrade-cured Biodentine, a cement-based dental material, is quantified experimentally by crushing cylindrical specimens with length-to-diameter ratios amounting to 1.84 and 1.34, respectively, at nine different material ages ranging from 1 h to 28 days. After excluding strength values significantly affected by imperfections, formulae developed for concrete are i) adapted for inter- and extrapolation of measured strength values, and ii) used for quantification of the influence of the slenderness of the specimens on the compressive strength. The microscopic origin of the macroscopic uniaxial compressive strength of mature Biodentine is investigated by means of a micromechanics model accounting for lognormal stiffness and strength distributions of two types of calcite-reinforced hydrates. The following results are obtained: The material behavior of Biodentine is non-linear in the first few hours after production. After that, Biodentine behaves virtually linear elastic all the way up to sudden brittle failure. The strength evolution of Biodentine can be well described as the exponential of a function involving the square root of the inverse of the material age. The genuine uniaxial compressive strength evolution can be quantified using a correction formula taken from a standard for testing of concrete, which accounts for length-to-diameter ratios of cylindrical samples deviating from 2. Multiscale modeling suggests that 63% of the overall material volume, occupied by dense calcite-reinforced hydration products, fail virtually simultaneously. This underlines the highly optimized nature of the studied material.